Tinjauan Hukum Islam terhadap Pembayaran Gaji Guru menggunakan Sistem Garap Sawah - Putri, Nanda Silvia (CV Global Research Publication, 2025)
This study examines the practice of teachers' salary payments using a rice field cultivation system at MI Mathlaul Anwar Kertasana from an Islamic law perspective. The research background is the use of waqf land as a source of operational funding, including teacher salaries, where teachers are given the right to cultivate rice fields and take the harvest as their wage (ujrah). This research was conducted using a qualitative method with a case study approach. Data was collected through interviews and literature review, then analyzed descriptively using the principles of ijarah in Islamic jurisprudence. The results show that the practice does not fully meet the pillars and conditions of the ijarah contract, especially concerning the certainty of the wage amount (ujrah), which is dependent on fluctuating harvest yields. This creates an element of uncertainty (gharar) and has the potential for injustice. The study concludes that while the intention is good, the mechanism needs to be improved to align with Sharia principles, particularly regarding clarity, certainty, and fairness in wage determination.